Pediatric and adolescent sports medicine - Saperstein, A. L.; Nicholas, S. J. (Pediatric Clinics of North America, 1996)
The majority of pediatric sports-related injuries are relatively benign and are easily treated with conservative measures. When surgical intervention is required, it is usually effective in returning the athlete to participation within a reasonable time frame. Effective care of pediatric athletes, however, involves not only knowledge of the many types of injuries and their treatments but also insight into the demands of the various sports and the needs of individual athletes. Treatment and resumption of participation recommendations frequently vary depending on the patient's sport, level of participation, and willingness to substitute alternative sports for his or her primary one. As always, individualizing treatment leads to greater patient satisfaction and improved results.